Fe-loaded biochar obtained from food waste for enhanced phosphate adsorption and its adsorption mechanism study via spectroscopic and experimental approach - Kang, Jin Kyu; Seo, Eun Jin; Lee, Chang Gu; Park, Seong Jik (Journal of Environmental Chemical Engineering, 2021)
The re-utilization of food waste is an eco-friendly method for valorizing waste. In this study, food waste was blended with iron (Fe-FW) and optimized using the response surface methodology (RSM) to produce Fe-loaded food waste biochar (Fe-FWB); moreover, the waste was utilized to probe the adsorption of phosphate in water, where pyrolysis time (1.0, 2.5, and 4.0 h), temperature (300, 450, and 600 °C), and Fe concentrations (0.1, 0.3, and 0.5 M) were set as independent variables. After optimizing the Fe-FWB, batch experiments were performed to examine the phosphate sorption characteristics of Fe-FW and Fe-FWB. A pseudo-second order and Elovich kinetic model thoroughly explained the adsorption kinetics, which was indicative of the rate-limited sorption via diffusion or surface coverage after the rapid initial adsorption. The Freundlich and Redlich-Peterson isotherm models more accurately simulated the adsorption of phosphate onto Fe-FW and Fe-FWB than the Langmuir isotherm model. The thermodynamic results presented a positive value of ΔG0, clearly indicating that the reaction was not spontaneous; positive values of ΔH0 and ΔS0 affirmed the endothermic characteristic of phosphate uptake into Fe-FW and Fe-FWB, with an increase in randomness. The adsorption of phosphate onto Fe-FW and Fe-FWB decreased as the solution pH increased from 3 to 11. In the presence of interfering anions, phosphate adsorption onto Fe-FWB was influenced by the coexistence of HCO3-, SO42-, and NO3-. These results suggest that the synthesized Fe-loaded food waste biochar can be used as an emerging adsorbent for phosphate removal from aqueous solutions.
Keywords: Adsorption mechanism; Bio chars; Experimental approaches; Food waste; Iron loading; Mechanism studies; Optimizing experimental condition; Phosphate adsorption; Positive value; Response-surface methodology; Biochar; Food waste; Iron loading; Optimizing experimental conditions; Phosphate; Response surface methodology